2012
DOI: 10.1584/jpestics.g11-02
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and phytotoxic activity of novel acylthiourea and 2H-1,2,4-thiadiazolo[2,3-.ALPHA.]pyrimidine derivatives

Abstract: Eight N- [3-(2,4-dichlorophenyl)-5-methylisoxazol-4-ylcarbonyl]-N′-(4,6-disubstituted pyrimidin-2-yl)thioureas and eight 5,7-disubstituted-2-[3-(2,4-dichlorophenyl)-5-methyl isoxazol-4-ylcarbonylimino]-2H-1,2,4-thiadiazolo[2,3-α]pyrimidines were synthesized by multi-step reactions in yields of 50-85%. The structures of the target compounds were confirmed by IR, 1 H NMR spectra and elemental analyses. Phytotoxic activities against Echinochloa crus-galli L., Digitaria ciliaris L., Brassica napus L. and Chenopodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…[343] Their insecticidal activities against oriental armyworm (Mythimna separata), mosquito larvae (Culex pipiens pallens) and diamondback moth (Plutella xylostella) were evaluated and indicated that the introduction of the 1-(acyl) thiourea group into some structures is important for retention of insecticidal activity. [343] N- [3-(2,4-dichlorophenyl)-5-methylisoxazol-4-ylcarbonyl]-N -(4,6-di-substituted pyrimidin-2-yl)thioureas [344] exhibit good phytotoxic activity against Echinochloa crusgalli L., Digitaria ciliaris L., Brassica napus L. and Chenopodium serotinum L.…”
Section: Biological Aspectsmentioning
confidence: 99%
“…[343] Their insecticidal activities against oriental armyworm (Mythimna separata), mosquito larvae (Culex pipiens pallens) and diamondback moth (Plutella xylostella) were evaluated and indicated that the introduction of the 1-(acyl) thiourea group into some structures is important for retention of insecticidal activity. [343] N- [3-(2,4-dichlorophenyl)-5-methylisoxazol-4-ylcarbonyl]-N -(4,6-di-substituted pyrimidin-2-yl)thioureas [344] exhibit good phytotoxic activity against Echinochloa crusgalli L., Digitaria ciliaris L., Brassica napus L. and Chenopodium serotinum L.…”
Section: Biological Aspectsmentioning
confidence: 99%
“…It is well known that pyrimidine core has wide occurrence in nature 4 , and which has also represent a typical class of heterocyclic scaffold in various compounds applied in the field of medicinal chemistry 5 6 7 8 9 10 11 12 13 14 15 , agrochemicals 16 17 18 19 20 21 22 23 24 , and materials 25 26 27 28 29 . Up to now, many pyrimidines analogues have been demonstrated to exhibit wide pharmacological activities mainly including anticancer, antiviral, antibacterial, antimalarial, antituberculosis activities.…”
mentioning
confidence: 99%
“…Nitrogen is the most favorite heteroelement in life science research, and heterocyclic compounds containing N attract great interest of the researchers . Naphthyridine is an important member of N‐containing compounds, and its derivatives have gained special attention of researchers on account of their variety of interesting biological activities in medicinal chemistry.…”
Section: Introductionmentioning
confidence: 99%